PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY : PERAN PEMODERASI DEWAN KOMISARIS: DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY : THE MODERATING ROLE OF THE BOARD OF COMMISSIONERS - Hedar Rusman (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
This study00aims to empirically analyze the moderating role of the board of commissioners by under effects of profitability, liquidity, and leverage on corporate social responsibility disclosure. Data analysis using multiple linear regression method with 128 samples of a manufacturing company from 2016-2018 and listing at BEI Jakarta. This study showed that real earning management, profitability, and liquidity positively impact corporate social responsibility disclosure, while leverage has a negative impact on corporate social00responsibility disclosure. In addition, that board of commissioners has been strengthened by the effect of real earning management and liquidity on corporate social responsibility disclosure. That board00of commissioner has not been strengthened by the effects of profitability and liquidity on corporate social responsibility disclosure. On the other hand, it also to showed that the board of commissioners had not been weakened by the effect of leverage on corporate social responsibility disclosure